(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
Contemporary surveillance regimes no longer rely on concealment but operate through hypervisibility, subsuming subjects into networks of algorithmic governance where exposure functions as a mode of control. The present article interrogates the aesthetic and political stakes of artistic resistance to platform capitalism’s algorithmic governance, examining the shift from critical complicity – where artists tactically repurpose surveillance technologies from within – to radical exteriority, an aesthetic strategy that seeks to evade incorporation into surveillance systems altogether. Drawing on media theory, digital aesthetics, and platform studies, the contribution discusses how contemporary artistic interventions engage, subvert, or evade algorithmic governance. It includes a discussion of works by Hito Steyerl, Paolo Cirio, Trevor Paglen, James Bridle, and Holly Herndon, and explores whether counter-surveillance aesthetics can generate true resistance or risk assimilation into predictive systems, arguing that while artistic subversion often reinforces surveillance capitalism’s logics, emergent strategies – tactical illegibility, algorithmic obfuscation, and infrastructural reconfiguration – may offer new avenues of resistance. Ultimately, the paper situates counter-surveillance art within a broader critique of digital capitalism, questioning whether contemporary aesthetics can carve out zones beyond algorithmic capture or remain ensnared in the infrastructures they seek to contest. The future of artistic resistance, it contends, hinges not on critique alone, but on the speculative construction of post-surveillance paradigms.